Canons and Heroes: The Reception of the Complete Works Translation Project in Finland, 2002-13 - Keinänen, Nely (Multicultural Shakespeare: Translation, Appropriation and Performance, 2017)
This essay examines the reception of the ten-year Complete Works translation project undertaken by the Finnish publishing company Werner Söderström Oy (WSOY) in 2004-13. Focusing on reviews published in the first and last years of the project, the essay details ongoing processes of Shakespeare (re-)canonization in Finland, as each new generation explains to itself what Shakespeare means to them, and why it continues to read, translate and perform Shakespeare. These processes are visible in comments from the series editors and translators extolling the importance of Shakespeare’s work and the necessity of creating new, modern translations so Finns can read Shakespeare in their mother tongue; in discussions of the literary qualities of a good Shakespeare translation, e.g. whether it is advisable to use iambic pentameter in Finnish, a trochaic language; and in the creation of publisher and translator “heroes,” who at significant cost to themselves, whether in money in terms of the publisher, or time and effort in terms of the translators, labour to provide the public with their Shakespeare in modern Finnish. While on the whole reviewers celebrated the new translations, there was some resistance to changes in familiar lines from older translations, such as Macbeth’s “tomorrow” speech, suggesting that there are nevertheless some limits on modernizing “classic” translations.